2023
DOI: 10.1111/jdv.18880
|View full text |Cite
|
Sign up to set email alerts
|

Lentigo maligna (melanoma): A systematic review and meta‐analysis on surgical techniques and presurgical mapping by reflectance confocal microscopy

Abstract: Because of an increased risk of local recurrence following surgical treatment of lentigo maligna (melanoma) (LM/LMM), the optimal surgical technique is still a matter of debate. We aimed to evaluate the effect of different surgical techniques and reflectance confocal microscopy (RCM) on local recurrence and survival outcomes. We searched MEDLINE, Embase and PubMed databases through 20 May 2022. Randomized and observational studies with ≥10 lesions were eligible for inclusion. Bias assessment was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…Another study, with a mean follow-up of 5.1 years, reported a recurrence rate of 3% developed at mean 2.9 years [ 56 ]. This is a lower recurrence rate than previously reported in LM treated with WE (6–20%) [ 85 , 86 , 87 ], and closer to that reported in those treated by surgery with microscopic margin control, both MMS and SE (0–3%) [ 85 , 86 , 87 , 88 ].…”
Section: Immunotherapy In Melanoma In Situsupporting
confidence: 78%
“…Another study, with a mean follow-up of 5.1 years, reported a recurrence rate of 3% developed at mean 2.9 years [ 56 ]. This is a lower recurrence rate than previously reported in LM treated with WE (6–20%) [ 85 , 86 , 87 ], and closer to that reported in those treated by surgery with microscopic margin control, both MMS and SE (0–3%) [ 85 , 86 , 87 , 88 ].…”
Section: Immunotherapy In Melanoma In Situsupporting
confidence: 78%
“…Many studies have explored the RCM characteristics of MM, 1 , 4 , 5 including melanoma in specific locations such as lentigo maligna melanoma. 6 , 7 , 8 However, monitoring acral skin using RCM is challenging because of the thick stratum corneum of the extremities; there are few reports describing the RCM characteristics of acral melanoma. In this study, RCM showed a sensitivity of 100% for the diagnosis of ALM, which was higher than that of histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…However, surgical treatment of LM is associated with an increased risk of local recurrence compared with other subtypes of melanoma, as a result of incomplete resection. Unexpected positive margins are caused by the frequent subclinical extension of atypical cells [18]. Following WLE with the recommended 5 mm surgical margins, studies report recurrence rates that vary from 6% to 20%.…”
Section: Wide Local Excisionmentioning
confidence: 99%
“…A systematic review and metaanalysis on surgical techniques in LM showed that a 5 mm surgical margin resulted in negative histological margins in 83% of cases following WLE or staged excision with partial margin assessment, while after complete histological assessment, the margins were found to be involved in 59% of cases. The weighted mean of a surgical margin needed for a negative histological margin was 7.7 ± 2.00 mm [18]. As a consequence, newer guidelines acknowledge the need to use clinically measured surgical margins larger than 5 mm (i.e., 5-10 mm) in order to achieve local control.…”
Section: Wide Local Excisionmentioning
confidence: 99%
See 1 more Smart Citation